2007
DOI: 10.1194/jlr.m600258-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lipase activities by basic polysaccharide

Abstract: Basic polysaccharide strongly inhibited the hydrolysis of trioleoylglycerol (TO) emulsified with phosphatidylcholine and taurocholate by either pancreatic lipase or carboxylester lipase. DEAE-Sephadex dose-dependently inhibited the hydrolysis of TO by pancreatic lipase and carboxylester lipase; however, carboxymethyl-Sephadex and Sephadex G-50 did not inhibit the hydrolysis. Polydextrose (PD), a soluble polysaccharide, was a very weak inhibitor of pancreatic lipase. However, when a basic group, a DEAE group, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 17 publications
1
31
1
Order By: Relevance
“…Therefore, poorly fermented fiber sources that reduce resident time, such as chitosan, should lower the in vivo absorption of environmental contaminants. In contrast, it has been reported that chitosan can inhibit pancreatic lipase activity, 25) and there was a significant negative correlation between rates of fecal EDCs and apparent fat digestibility in our study. Based on these factors, the mechanism of chitosan's effect in promoting fecal EDC excretion might include inhibition of fat absorption and of the EDCs dissolved in fat.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Therefore, poorly fermented fiber sources that reduce resident time, such as chitosan, should lower the in vivo absorption of environmental contaminants. In contrast, it has been reported that chitosan can inhibit pancreatic lipase activity, 25) and there was a significant negative correlation between rates of fecal EDCs and apparent fat digestibility in our study. Based on these factors, the mechanism of chitosan's effect in promoting fecal EDC excretion might include inhibition of fat absorption and of the EDCs dissolved in fat.…”
Section: Discussioncontrasting
confidence: 54%
“…Furthermore, it has been reported that chitosan can inhibit pancreatic lipase activity. 25) In this study, therefore, the effect of chitosan intake in promoting fecal fat and fecal lipophilic EDC excretion is thought to have been due to the inhibition of absorption of them by chitosan, inhibiting pancreatic lipase activity and fat absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that highly flocculated lipid droplets are digested more slowly than non-flocculated ones because of a reduction in the surface area of lipid phase directly exposed to the lipase molecules (Day et al, 2014). The adsorption of bile salts to oil droplet surfaces (and displacement of the original surfactants) is often critical to lipid digestion, as the formation of a bile-salt coated interface promotes lipase adsorption and activation (Aloulou et al, 2006;Borgström & Brockman, 1984;Tsujita et al, 2007). Moreover, the activity of lipase is determined by the amount that adsorbs to the lipid droplet surfaces, rather than the total amount present in the system (Moreau, Moulin, Gargouri, Noel, & Verger, 1991;Ransac et al, 1997;Tsujita et al, 2007).…”
Section: Free Fatty Acid Formation During Lipolysismentioning
confidence: 98%
“…The adsorption of bile salts to oil droplet surfaces (and displacement of the original surfactants) is often critical to lipid digestion, as the formation of a bile-salt coated interface promotes lipase adsorption and activation (Aloulou et al, 2006;Borgström & Brockman, 1984;Tsujita et al, 2007). Moreover, the activity of lipase is determined by the amount that adsorbs to the lipid droplet surfaces, rather than the total amount present in the system (Moreau, Moulin, Gargouri, Noel, & Verger, 1991;Ransac et al, 1997;Tsujita et al, 2007). When no ε-PL is present, bile salts are free to interact with the oil droplets, establishing suitable conditions on the droplet surfaces for the subsequent adsorption and activation of lipase.…”
Section: Free Fatty Acid Formation During Lipolysismentioning
confidence: 99%
“…Previous studies have demonstrated that administration of a lipase inhibitor (17,18) significantly increases total lipid excretion in feces in a dose-dependent manner. It is assumed that the lipid that is not absorbed from the small intestine is excreted in the feces.…”
Section: Discussionmentioning
confidence: 99%